Validity and Reliability of Least Preferred Coworker (LPC) Scale - Arjanto, Paul; Burhanuddin, Burhanuddin; Sumarsono, Raden Bambang (International Research-Based Education Journal, 2022)
The purpose of this study was to test the validity and reliability of the Least Preferred Coworker (LPC) Scale in Indonesia. LPC is a self-report instrument that measures the level of relationship between coworkers. Validation was carried out with a sample of 244 respondents spread throughout Indonesia. The results showed that the LPC has a reliability index with Cronbach's Alpha is 0.754 and the validity by factor analysis shows KMO and Bartlett's Test 0.818 with a significance of 0.000 and an anti-image correlation value > 0.5. Formed 1 factor that can explain 46.875% of the variability. factor loading ( factor loading ) of each item between 0.186 - 0.808. The results of this study indicate that LPC can be used as a valid and reliable instrument for measuring the level of relationship between coworkers.